CORRELATION OF TEMPOROMANDIBULAR JOINT CHANGES IN REPRODUCTIVE-AGE FEMALE PATIENTS ACCORDING TO THE PATHOGENETIC CLASSIFICATION - Novikov, V.M.; Pankevych, A.I.; Gogol, A.M.; Kolisnyk, I.A.; Rezvina, K.Yu.; Korostashova, M.A. (World of Medicine and Biology, 2024)
The study addresses the relationship between gynecological factors and the progression of osteoarthritis of the temporomandibular joint, focusing on pathogenesis-based classification of intra-articular temporomandibular joint disorders. The research involved analyzing clinical and hormonal data from female patients, emphasizing the impact of reproductive health on temporomandibular joint pathology. The findings revealed a significant correlation between specific gynecological conditions and the severity of temporomandibular joint osteoarthritis, highlighting the importance of considering reproductive health in the management and diagnosis of temporomandibular joint disorders. This study contributes to global science by proposing a novel perspective on the interconnection between gynecological factors and temporomandibular joint pathology, which could influence future diagnostic and therapeutic approaches.